Supporting Stroke Rehabilitation Through Gamified Daily Activity Simulations - Barboza, Lucas D.; Silva, Franciely R. da; Oliveira, Humberto G. de; Oliveira, Jullia C. de; Brasil, Antônio R. A. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais Estendidos do XXV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2025.6923, 2025)
This paper introduces the creation of an open-source virtual reality (VR) game for stroke rehabilitation by simulating daily activities. The game proposes immersive environments, including a tea room, bathroom, garden, and kitchen, designed to promote functional gesture movements and enhance user engagement by introducing gamification. Patients are rewarded with points for task completion, for example, grabbing a fruit and eating, thus creating a competitive and motivating environment. Preliminary testing with university students received positive responses, particularly regarding the realism of the tasks. However, extended use of VR resulted in reports of physical discomfort and headaches. Next steps include the approval for further testing by the Ethics Committee involving stroke patients.